PENINGKATAN KINERJA MESIN PENCACAH BRONDOLAN SAWIT - Adam Arfandi; Ahmad Arjuna; Maulana M Ibrahim; Angga Sateria (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Oil palm is an important industrial oil-producing plant that can reach 24 meters in height. The area of ​​​​oil palm plantations continues to increase in several areas in Indonesia. One of them is in the Bangka Belitung area which continues to increase rapidly every year. The area of ​​​​oil palm plantations in the province of Bangka Belitung continues to increase every year, recorded in 2021 reaching 238.60 thousand hectares, so one of the five oil palm plantations is palm kernels. Oil palm kernels are one of the wastes from oil palm plantations that can be used to make animal feed and have a lot of concentrate. Therefore, in this final project, the Performance Improvement of the Palm Oil Palm Oil Chopping Machine is designed with improvements that occur in the spacer which is easy to disassemble and the thickness of the machine. spacer, hopper formation and thickness cutting edge. This palm loose fruit chopper is capable of chopping up to 90 kg/hour of palm loose fruit with a length of 0.8-3 cm of coir.